214k views
2 votes
If f(x) = -5n + 1 and g(x) = -6n + 2, find (f + g)(-2).-182325-25

If f(x) = -5n + 1 and g(x) = -6n + 2, find (f + g)(-2).-182325-25-example-1
User Wallgeek
by
4.9k points

1 Answer

6 votes

Determine the expression for (f + g)(x).


\begin{gathered} (f+g)(x)=f(x)+g(x) \\ =-5n+1-6n+2 \\ =-11n+3 \end{gathered}

Substitute -2 for n in the equation to obtain the value of (f + g)(-2).


\begin{gathered} (f+g)(-2)=-11\cdot(-2)+3 \\ =22+3 \\ =25 \end{gathered}

So answer is 25.

User Farbiondriven
by
4.7k points